2019
DOI: 10.1155/2019/9732325
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Environmental Factors in Regulation of Oxidative Stress in Plant

Abstract: Exposure to a variety of environmental factors such as salinity, drought, metal toxicity, extreme temperature, air pollutants, ultraviolet-B (UV-B) radiation, pesticides, and pathogen infection leads to subject oxidative stress in plants, which in turn affects multiple biological processes via reactive oxygen species (ROS) generation. ROS include hydroxyl radicals, singlet oxygen, and hydrogen peroxide in the plant cells and activates signaling pathways leading to some changes of physiological, biochemical, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
182
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(198 citation statements)
references
References 135 publications
(142 reference statements)
9
182
0
7
Order By: Relevance
“…Environmental stresses (such as drought, cold stress, salt stress, and pathogen attack) are often accompanied by leaf abscission [15][16][17], but the relationship between stress and abscission is rarely studied. Excessive ROS can damage cellular components, including lipids, protein, and nucleic acids [18]. ROS produced at the abscission zone site play an important role in regulating leaf abscission under drought stress in cassava (Manihot esculenta Crantz) [19].…”
mentioning
confidence: 99%
“…Environmental stresses (such as drought, cold stress, salt stress, and pathogen attack) are often accompanied by leaf abscission [15][16][17], but the relationship between stress and abscission is rarely studied. Excessive ROS can damage cellular components, including lipids, protein, and nucleic acids [18]. ROS produced at the abscission zone site play an important role in regulating leaf abscission under drought stress in cassava (Manihot esculenta Crantz) [19].…”
mentioning
confidence: 99%
“…H 2 O 2 is a major redox metabolite and at high concentrations induces oxidative damage to biomolecules (Cerny et al , 2018). To avoid oxidative damage to cellular structures, plants mainly use enzymatic antioxidants, such as superoxide dismutases (SODs), catalases (CATs), and peroxidases (POXs), to scavenge H 2 O 2 (Xie et al , 2019). Our previous results showed that two peroxidase genes induced by BSR‐D1 are employed by M. oryzae to suppress blast disease resistance (Li et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, plant induces the expression of several isoforms of NHXs namely SOS1, NHX1, NHX2, NHX3 and NHX6 under salt stress to regulate Na + fluxes in and out of the cell (Dragwidge et al, 2018). Upon salt stress, plants activate a complex antioxidant defense mechanism to minimize oxidative stress damage by ROS under salt stress conditions (Xie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%